Safety and efficacy of transvenous mechanical lead extraction in patients with abandoned leads. Issue 9 (18th July 2020) - Segreti, Luca; Giannotti Santoro, Mario; Di Cori, Andrea; Fiorentini, Federico; Zucchelli, Giulio; Bernini, Giulia; De Lucia, Raffaele; Viani, Stefano; Paperini, Luca; Barletta, Valentina; Soldati, Ezio; Bongiorni, Maria Grazia
Abstract: Aims: Optimal management of redundant or malfunctioning leads is controversial. We aimed to assess safety and efficacy of mechanical transvenous lead extraction (TLE) in patients with abandoned leads. Methods and results: Consecutive TLE procedures performed in our centre from January 2009 to December 2017 were considered. We evaluated the safety and efficacy of mechanical TLE in patients with abandoned (Group 1) compared to non-abandoned (Group 2) leads. We analysed 1210 consecutive patients that required transvenous removal of 2343 leads. Group 1 accounted for 250 patients (21%) with a total of 617 abandoned leads (26%). Group 2 comprised 960 patients (79%) with 1726 leads (74%). The total number of leads (3.0 vs. 2.0), dwelling time of the oldest lead (108.00 months vs. 60.00 months) and infectious indications for TLE were higher in Group 1. Clinical success was achieved in 1168 patients (96.5%) with a lower rate in Group 1 (90.4% vs. 98.1%; P  < 0.001). Major complications occurred in only 9 patients (0.7%), without significant differences among the two groups. The presence of one or more abandoned leads [odds ratio (OR) 3.47; 95% confidence interval (CI) 1.07–11.19; P  = 0.037] and dwelling time of the oldest lead (OR 1.01 for a month; 95% CI 1.01–1.02; P  < 0.001) were associated with a higher risk of clinical failure. Conclusion: Transvenous mechanical lead extraction is a safe procedure also in high-risk settings, as patients with abandoned leads. Success rate resulted a bit lower, especially in the presence of abandoned leads with long implantation time.